Ten Year Trends in Faculty Members\' Evaluation Results in Jondi Shapour University of Medical Sciences - Abdolhossein Shakournia; Hossein Elhampour; alireza mozafari; Bahman DashtBozorgi (مجله ایرانی آموزش در علوم پزشکی, 2008)
Introduction: A comprehensive and valid evaluation system with continuous performance is required in order to assess faculty members' educational practice correctly, and plan for quality improvement. This study was done to determine the ten year trends in faculty members' evaluation results in Jondi Shapour University of Medical Sciences. Methods: In a cross-sectional study, evaluation scores of 84 non-clinical faculty members of Jondi Shapour University of Medical Sciences, from 1996 till 2005 were investigated. Faculty members' evaluation scores were taken from the archive of Educational Development Center of the University and were analyzed by SPSS software using repeated measure ANOVA, Pearson correlation coeficient, and t-test. Results: The trends in evaluation scores had minimal changes between 3.95 and 4.02. The mean of faculty members' evaluation scores had no significant difference in different years. Also, the mean of the evaluation scores of male and female faculty members in different years showed no significant difference. Pearson correlation coeficient showed a weak to average correlation between faculty members' evaluation scores in some of the years. (0.22 at minimum and 0.65 at maximum). Conclusion: Faculty members' evaluation by students was invariable in 10 years, despite the fact that students population performing the evaluation, had changed during the period. It is necessary to revise the method of educating teaching skills to faculty members in order to improve their evaluation scores.